Design and content validity of a socioformative rubric to evaluate investigative skills in postgraduate - Aliaga Pacora, Alicia Agromelis (2021)
In the present investigation, an instrument for evaluating postgraduate research competencies was designed and validated in content. For its design, aspects evidenced in the development of the thesis work were integrated. The instrument was reviewed by four experts for the facie validity analysis and an expert judgment was made for the content validity analysis. At the end of these phases, an instrument was piloted with 38 advisers to assess the degree of understanding of instructions and items, as well as the reliability of the instrument. The instrument was designed as a socio-formative analytical rubric integrating five aspects of the development of the thesis work through 11 items and for each of them five levels of performance with their own descriptor. The experts expressed writing suggestions to optimize the rubric. The expert judges validated the items in content (Aiken's V> 0.80; LV CI 95%>0.75). The piloting showed a good degree of understanding of the instructions and items and relevance of the questions and it was determined that the instrument has reliability (Cronbach's Alpha: 0.832). A valid content instrument is presented; however, it is necessary to continue with the analysis of its psychometric properties (construct validity and reliability)